PHONOLOGICAL PROCESSES IN SELECTED NIGERIAN CHILDREN’S SPOKEN ENGLISH IN OYO AND LAGOS STATES, NIGERIA (2021)
Phonological processes constitute a veritable means to tracing language development, especially in children. Extant studies on Nigerian children’s phonological processes have examined errors and deviations, with little attention to language as an instrument for measuring children’s linguistic development. Therefore, this study was designed to examine children’s phonological processes and the constraints ranking responsible for them, with a view to tracing their linguistic development. Alan Prince and Paul Smolensky’s Optimality Theory was used as the framework, while the descriptive design was adopted. One hundred and two participants were purposively selected. Seventy-five and twenty-five children from primary schools in Lagos and Oyo states, respectively, were selected because of their age range of four to six years, and they read a prepared text. The choice of the states was motivated by their proximal, cosmopolitan and multicultural features. Also, two children, named child A, aged one year-three months, and child B, aged four years-three months, were observed in their homes in Oyo and Lagos states, respectively, for six months for the purpose of longitudinal observation. All utterances were audio-recorded. Data were subjected to descriptive statistics, perceptual and acoustic analyses. The phonological processes identified were substitution (28.8%), vowel strengthening (23.2%), monophthongisation (15.7%), deletion (15.4%), assimilation (6.6%), gliding (4.3%) and yod coalescence (2.7%). Utterances were slow-paced, with an average of 4.8 minutes per participant, and phonemes were often singly produced. Constraints ranking favoured markedness over faithfulness constraints, such as *SCHWA >> αF, NODIPHTHONG >> MAX, *Ct#C >> *COMPLEX >> MAX and AGREE(PLACE) >> IDENT-IO. The participants’ linguistic development was noticeable in the instantiations of their processes, which were similar to the ambient variety of Nigerian English. The instances were very intelligible and significantly manifested beyond word level. They were also functional for achieving juncture prosody, cluster reduction and gemination. However, non-adult instances, like morphophonemic deletions, persisted, showing that the participants had not fully attained the adult level of phonological processes. In the longitudinal data, child A acquired voiced and labial consonants first, and codas suffered deletion more than onsets in monosyllables. By age two, child A had begun to produce polysyllables and closed syllables, and deletion changed from whole syllables to only phonemes. By age five, child B’s processes had begun to resemble adults’ and, more energy-demanding processes like epenthesis, voicing and vowel strengthening emerged. Tonalisation of English words and indigenous interference occurred in their utterances. The spectrogram showed that the outset of acquisition with child A featured weaker energy, like in unaspirated plosives; however, energy increased and stabilised as the participant got older, as indicated in the darker shades. The formant values of the participants’ vowels on the acoustic chart showed similarity to the cardinal vowel chart in terms of height and position of the tongue. Phonological processes in Nigerian children’s spoken English emerged through constraints reranking and increasingly become more like adults’ as the years pass by.